How silence facilitates verbal participation - Nguyen Thanh-My; Dat Bao (English Language Teaching Educational Journal, 2020)
The article reports a qualitative-quantitative case study of 239 Vietnamese university students’ perspectives on the effects of their silence on the formulation and quality of their talk. It presents participants’ voices with regards to whether and how their silent thinking influences verbal communication in the English language classroom and discusses the dynamics of productive learning strategies that would benefit the quality of speech. Data from an open-ended questionnaire reveal insights into students’ silent and verbal learning with a focus on the logical relationship between the two modes. Three findings coming out of this project include different nuances of the silent learning behaviour, the frequency of success in producing speech after mental processing practice, and a range of practical strategies that helps turn thoughts into verbal output. The study unpacks the importance of silence as autonomous learning and proposes relevant classroom activities for more rewarding outcomes.